Reconstruction of Criminal Sanctions On Actors Of Online Prostitution Based On Justice Value - Ratih Mega Puspasari (Law Development Journal, 2019)
Cybercrime is one shape is one of the dark side of technological progress. One form of crime in the area of cybercrime that is online prostitution. In the positive law in Indonesia only prohibits those helping and providing illegal sexual services, meaning that the prohibition only given to pimps, brokers, and prostitutes while users of commercial sex itself is absolutely no chapters that govern them. The purpose of this study to find out the settings in Indonesian positive law against online prostitution service users and to determine judicial review against online prostitution service users based on the positive law in Indonesia. Research conducted in this thesis is a normative legal research. This study used the approach of legislation and the comparative approach. Legal materials used are the primary legal materials, secondary and tertiary. Further legal material collection techniques in this research is literature study, then do a normative analysis of qualitative and describe it in the form of research. The survey results revealed that the arrangement of positive law in Indonesia to service users are not yet effective in the trap and tackling online prostitution, because it did not regulate the service users in an online prostitution a criminal offense. Overview jurisdiction over the online prostitution by No. 11 of 2008 on Information and Electronic Transactions and Act No. 44 Of 2008 on Pornography does not mention the provisions on service users online prostitution in particular, so that the two laws even this can’t ensnare the service user online prostitution.Keywords: Reconstruction; Criminal Sanctions; Online Prostitution; Justice.